PATIENT SAFETY: A SURVEY OF KNOWLEDGE OF GENERAL PRACTITIONERS IN KARACHI: Patient Safety (A Survey) - Azam, Naila; Hassan, Uzma; Khan, Najm-us-Saqib; Javed, Asghar (Pakistan Armed Forces Medical Journal, 2014)
Objective: To study the knowledge of General Practitioners on Patient’s Safety.Study Design: Descriptive cross sectional study.Place and Duration of Study: Malir district, Karachi, from Feb 2012 to April 2012.Material and Methods: Response to a closed ended questionnaire by general practitioners (GPs) was recorded using non probability convenient sampling .The variables were derived from aspects of patient safety issues. The questionnaire used 11 potential risk factors to explore GPs’ views on patient safety.Results: A total of 68 GPs responded out of the total 150 GPs running their private clinics or filter clinics of private hospitals in the Malir district area. The risk factors most frequently judged as a threat to patient safety were a poor doctor-patient relationship, insufficient continuing education on the part of the GP and a patient age based guidelines and patient privacy in the reception/waiting room were not perceived as risk factors by most of the GPs.Conclusion: GPs in the present study judged a broader range of factors than in previously published research on patient safety in primary care, including a poor doctor-patient relationship, to pose a potential threat to patient safety. Other risk factors such as infection prevention, deviation from guidelines and incident reporting were judged to be less relevant than considered conventionally.